Reciprocity and R&D search: Applying the behavioral theory of the firm to a communitarian context. (15th May 2013) - O'Brien, Jonathan P.; David, Parthiban
<x xml:space="preserve">Abstract</x> We propose that the behavioral theory of the firm perspective on R&D search requires modification when applied to "communitarian" cultures such as Japan because reciprocity and embeddedness can influence the search decision. When performance exceeds aspirations, communitarian‐oriented firms are more inclined to use their privileged position to help their less fortunate stakeholders by engaging in additional R&D search that should yield greater payoffs for these stakeholders in the future. Our results indicate that while Japanese firms engage in "problemistic" search in a manner similar to what has been found in other contexts, they respond differently when performance exceeds expectations. We find that as performance rises above aspirations, communitarian‐oriented firms raise R&D search to a greater extent than do firms that lack a communitarian orientation. Copyright © 2013 John Wiley & Sons, Ltd.